Indonesia Perancangan Sistem Informasi Penjualan Berbasis Dekstop Studi Kasus Toko Fortuner Gorontalo - Sidik, Zainudin; Ismail, Abdul Rahman (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Technological advancements and information development are currently growing very rapidly. Information is very important for the development of information technology, because accurate information speeds up processes and vice versa. It is expected that this information technology advancement will help in optimizing data processing in Fortuner stores. This study uses a descriptive methodology used to gather requirements from the sales system. Document records that have been obtained are then examined and analyzed to be used as a desktop application design. Two program components developed are the admin view (Process and Transaction) and the consumer view (Order). The Visual Basic programming language is used to create the application, and several plugins are added to the application view for MySQL database storage. The application created can improve efficiency and accelerate the service and sales process with the results of blackbox testing all features can run as expected.